An effective self-control strategy for the reduction of aflatoxin M1 content in milk and to decrease the exposure of consumers. Issue 12 (1st December 2016) - Kerekes, Kata; Bonilauri, Paolo; Serraino, Andrea; Giacometti, Federica; Piva, Silvia; Zambrini, Vittorio; Canever, Alessandra; Farkas, Zsuzsa; Ambrus, Árpád
ABSTRACT: The study reports the results of testing the sensitivity of an early warning sampling plan for detecting milk batches with high aflatoxin AFM1 concentration. The effectiveness of the method was investigated by the analysis of 9017 milk samples collected in Italian milk processing plants that applied control plans with different action limits (AL). For those milk processing plants where 30 ng kg −1 AL has been applied, the AFM1 contamination was significantly lower at or above the 95th percentile of the milk samples when compared with plants that used 40 ng kg −1 AL. The results show that the control plan can be used effectively for early warning of occurrence of high AFM1 contamination of milk and to carry out pro-active measures to limit the level of contamination. Estimation of dietary exposure was also carried out, based on the aflatoxin M1 content of the milk samples and on Italian food consumption data. Estimated Daily Intakes (EDI) and Hazard Indices (HI) were calculated for different age groups of the population. HIs show that no adverse effects are expected for the adult population, but in the case of children under age three, the approximate HI values were considerably higher. This underlines the importance of the careful monitoring and control of aflatoxin M1 in milk and dairy products.